2013
DOI: 10.1038/nn.3348
|View full text |Cite
|
Sign up to set email alerts
|

Merlin isoform 2 in neurofibromatosis type 2–associated polyneuropathy

Abstract: The autosomal dominant disorder neurofibromatosis type 2 (NF2) is a hereditary tumor syndrome caused by inactivation of the NF2 tumor suppressor gene, encoding merlin. Apart from tumors affecting the peripheral and central nervous systems, most NF2 patients develop peripheral neuropathies. This peripheral nerve disease can occur in the absence of nerve-damaging tumors, suggesting an etiology that is independent of gross tumor burden. We discovered that merlin isoform 2 (merlin-iso2) has a specific function in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
55
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 33 publications
4
55
0
2
Order By: Relevance
“…It regulates diverse cellular processes, such as the establishment of cell polarity, formation of cell-cell junctions and proliferation. Nf2 plays numerous roles in the nervous system, including promoting cell-cell adhesion during neural tube closure (McLaughlin et al, 2007), inhibiting glial cell proliferation (Giovannini et al, 2000;Houshmandi et al, 2009) and maintaining axonal integrity (Schulz et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…It regulates diverse cellular processes, such as the establishment of cell polarity, formation of cell-cell junctions and proliferation. Nf2 plays numerous roles in the nervous system, including promoting cell-cell adhesion during neural tube closure (McLaughlin et al, 2007), inhibiting glial cell proliferation (Giovannini et al, 2000;Houshmandi et al, 2009) and maintaining axonal integrity (Schulz et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Work by Collard et al (1995) provided some of the first evidence for NF-H accumulations being a factor in the degenerative process of amyotrophic lateral sclerosis (ALS). More recent work by Schulz et al (2013) have shown that reduced phosphorylation of NF-H may be a contributing factor in neurofibromatosis type 2, and Sellner et al (2014) that NF-H may be a useful pathological and prognostic marker for acute encephalitis.…”
Section: Discussionmentioning
confidence: 99%
“…An additional mechanism is suggested by recent results: Two alternatively spliced merlin isoforms were found to be expressed in the mammalian nervous system, only one of which, isoform 2, was found in axons [12]. Functional studies revealed that an isoform 2-dependent complex promotes activation of the GTPase RhoA, leading to neurofilament heavy chain phosphorylation [12].…”
Section: Histopathology and Pathogenesismentioning
confidence: 99%